Imatinib resistance in chronic myelogenous leukemia: an emerging challenge - Khandelwal, Aparna; Kawatra, Mallika; Bhandari, Virendra; Yeshwante, Prashant S. (International Journal of Basic & Clinical Pharmacology, 2017)
Resistance to imatinib is a significant clinical issue, and the underlying mechanism of this resistance is multifactorial. The efficacy of imatinib in chronic myeloid leukemia (CML) in achieving a high remission rate and improving prognosis has seriously been challenged by the development of mutants of BCR-ABL gene, which resist the action of imatinib, which is a tyrosine kinase inhibitor. We present here a case of a 35-year-old male, a known case of CML on imatinib therapy, the patient eventually landed in blast crisis and succumbed to the disease and secondary infections.